SUMMARY: SOME FACTORS RELATED TO COMPLIANCE IN TREATMENT BASEDOW ON OUTPATIENTS (Vietnam Journal of Community Medicine, 2021)
Objective: Analyzing factors related to the compliance with Basedow disease treatment on outpatients at Can Tho City General Hospital. Objects and methods: The perspective research on 60 outpatients who come for re-examination at Can Tho City General Hospital from July, 1st, 2020 – September, 30th, 2020. Results: There was a statistically significant correlation between the patient’s duration of Basedow disease, the number of drugs prescribed in the prescription, the number of medications per day, drug beliefs and the level of compliance of treatment (p0.05). Conclusion: Factors of Basedow disease time of the patient, number of drugs prescribed in the prescription, number of medications per day, and belief in drugs to treat Basedow disease were related to compliance of treatment.